An empirical analysis of Colombia's trade liberalization process and its effect on the equilibrium of its structural trade deficit. Issue 2 (26th January 2022) - Abreo, Carlos; Bustillo, Ricardo; Rodriguez, Carlos
Abstract: This article examines the extent to which Colombia's trade liberalization, as a government strategy to boost its exports, has helped to balance its structural trade deficit. Based on the trade gravity model theory, we derive two‐way specifications (Colombian exports and imports) in order to analyze bilateral trade flows (fuels and non‐fuels) between Colombia and 136 countries from 2005 to 2018. Additionally, we compare the real export performance of Colombia with its main partners through the trade potential index (TPI), to assess the effect of Colombia's openness on bilateral trade. The econometric approach indicates that the free trade agreement (FTA) factor has a negative net effect on Colombia's exports and a positive net impact on Colombia's imports. Finally, the TPI analysis allows us to infer that although there is an evolution towards the intensification of Colombian trade, this trend is greater in imports than in exports, which suggests a deepening of the Colombian trade deficit.